Sleep-Disordered Breathing Is Associated With Reduced Left Atrial Strain Measured by Cardiac Magnetic Resonance Imaging in Patients After Acute Myocardial Infarction - Wester, Michael; Pec, Jan; Lebek, Simon; Fisser, Christoph; Debl, Kurt; Hamer, Okka; Poschenrieder, Florian; Buchner, Stefan; Maier, Lars S.; Arzt, Michael; Wagner, Stefan (Frontiers in Medicine, 2022)
Aims: Sleep disordered breathing (SDB) is known to cause left (LA) atrial remodelling. However, the relationship between the SDB severity and LA dysfunction is insufficiently understood and may be elucidated by detailed feature tracking (FT) strain analysis of cardiac magnetic resonance images (CMR). After myocardial infarction (MI), both the left ventricle and atrium are subjected to increased stress which may be substantially worsened by concomitant SDB that could impair consequential healing. We therefore analyzed atrial strain in patients at the time of acute MI and three months after. Methods and results: 40 patients with acute MI underwent CMR and polysomnography (PSG) within 3-5 days after MI. Follow-up was performed 3 months after acute MI. CMR cine data were analyzed using a dedicated FT software. Atrial strain (ε) and strain rate (SR) for atrial reservoir ([εs]; [SRs]), conduit ([εe]; [SRe]) and booster function ([εa]; [SRa]) were measured in two long-axis views. SDB was defined by an apnea-hypopnea-index (AHI) >15/h. Interestingly, LA εs and εe were significantly reduced in patients with SDB and correlated negative with AHI as a measure of SDB severity at both baseline and follow-up. Intriguingly, patients that exhibited a reduced AHI at follow-up were more likely to develop improved atrial reservoir and conduit strain (linear regression, p=0.08 for εs and εe). Patients with improved SDB (ΔAHI< -5/h) exhibited a mean improvement of LA reservoir strain of +7.2%±8.4% whereas patients with SDB deterioration (ΔAHI> +5/h) showed a mean decrease of -5.3%±11.0% (p=0.0131). Similarly, the difference for LA conduit function was +4.8%±5.9% (ΔAHI< -5/h) vs -3.6%±8.8% (ΔAHI> +5/h). Importantly, conventional volumetric parameters for atrial function (LA area, LA volume index) did not correlate with AHI at baseline or follow-up. Conclusion: Our results show that LA function measured by CMR strain but not by volumetry is impaired in patients with SDB during acute cardiac injury. Consistent with a mechanistic association, improvement of SBD at follow-up resulted in improved LA strain. LA strain measurement might thus provide insight into atrial function in patients with SDB.